"A Proposed Model of the Effect of Functional Burnout On the Performance of Employees and the Degree of Job Satisfaction" - القرني, علي; Al-Qarni, Ali (The Arab Journal of Administration, 2022)
The aim of this study to know the effect of functional Burnout on the performance of employees as a primary objective, to know the effect of functional Burnout on the degree of job satisfaction as a second main objective, and to know the effect of performance on job satisfaction. The Methodology: In this study, the researcher used Descriptive survey method Tools of the study: The researcher designed a questionnaire containing (50) words distributed on three main axes. And The study population consists of (150) employees of the Saudi Postal Corporation in Riyadh, the support services sector. The questionnaire was applied of (108) employees. The most important results of the study: 1- There is a negative correlation of statistical between the emotional stress and the working powers of employees of the Saudi Postal Corporation in Riyadh. 2-There is a negative correlation of statistical between the lack of humanity and the working powers of employees in the Saudi Postal Corporation in Riyadh. 3-There is a statistically significant negative correlation between emotional stress and job satisfaction among employees at Saudi Postal Corporation in Riyadh, where correlation coefficient is (0.64). 4- After the lack of humanity in the employees of the Saudi Postal Corporation in Riyadh can explain about (24%) of the changes in satisfaction with the employees of the Saudi Postal Corporation in Riyadh. 5-The personal achievement of employees at the Saudi Postal Corporation in Riyadh can explain about (36%) of the changes or effects that affect the satisfaction of the employees of the Saudi Postal Corporation in Riyadh.